Comparison of physiological responses in inline-speedskating to running and cycling. A simplification of exercise testing? - Hildebrand, C.; Mierau, J.; Joisten, F.; Strüder, H. K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Exercise testing is the basis for an individual targeted training and therefore indispensable in high performance sport. For optimal results, athletes are tested in a sport specific mode. However a specific inline-speedskating test poses some practical and methodological problems. Laboratory testing requires a special ergometer whereas field testing is only possible on a special skating track. Therefore, it was the aim of the study to investigate if results from more traditional exercise test in running or cycling can be transferred to inline-speedskating. Methods: For this reason we examined five male athletes (29 ± 3.9 years, 172.2 ± 5.9 cm and 69.3 ± 7.5 kg) of the top national level. The subjects performed three incremental exhaustive tests (ergometer cycling (EC), field running (FR), field inlinespeedskating (FIS)) in randomized order. The protocols were designed so that step duration and intensity increase were comparable. Oxygen uptake (VO2, absolute [l/min] and relative [ml/kg/min]), heart rate (HF [b/min]) and blood lactate concentration (LA [mmol/l]) were measured during each trial through a portable spirometry system (MetaMax 3B, Cortex, Germany). Results: Maximal values for absolute VO2 (p=0.06), LA (p= 0.49) and HF (p=0.63) were not significantly different for all three exercise modes. Only the relative VO2max differed significantly (p=0.02) between inline-speedskating (67.23) and cycling (82.04). At workloads corresponding to 2 and 4 mmol/l lactate no significant differences (p > 0.05) could be revealed for HF or VO2. Even for HF and LA at respiratory thresholds (ventilators threshold, respiratory compensation point) no significant differences (p > 0.05) could be detected. Conclusion: The results indicate that a cycling and running test revealed comparable physiological responses to an inline-speedskating test. Therefore we conclude that both a cycling and a running exercise test with the applied test protocol are a qualified alternative for an elaborate inline-speedskating test.